First principles study on p-type conductivity and new magnetic mechanism of ZnO:Sm with point defects in different strains. (1st June 2022) - Yang, Airong; Hou, Qingyu; Yin, Xiang; Qi, Mude; Wang, Zhichao
Abstract: Iterant electrons exist in the f and d states of ZnO:Sm with point defects (VZn, Hi ), which are often overlooked. Moreover, p-type ZnO is difficult to realize. To solve such problems, this study adopts the first-principles generalized gradient approximation (GGA + U) plane wave supersoft pseudopotential method to construct a ZnO:Sm system with point defects (VZn, Hi ). The stability and conductivity of the doped system and the new magnetic mechanism are studied under a biaxial strain. Result shows that the Zn34 SmHi O36 system has the lowest formation energy, simplest doping, lowest binding energy, and highest stability and is a relatively p-typed system when the Sm–H spacing is closer compared with the Zn34 SmHi O36 systems with different Sm–H spacings. The hole conductivity of the Zn34 SmHi O36 -doped system in the z-axis direction is high when no external strain is applied. The result demonstrates that the Zn34 SmHi O36 system is magnetic. The charge transfer from s state of single ion Sm to f and d states of Sm causes magnetism in the doped system, which differs from the traditional theory of orbital hybrid coupling and double exchange magnetic source between distinct ions. The Sm-4 f and Sm-5 d states in the Zn34 SmHi O36 system have itinerant and local electron properties, which affect the magnetic source and p-type of the system. This work has certain reference value for the design and preparation of new ZnO magnetoelectric-integrated functional materials. Highlights: Study on the p-type electrical conductivity of ZnO:Sm with point defects in different strains. The strains included doping, the lattice constant mismatch, and the mismatch of thermal expansion coefficient. The Zn34 SmHi O36 system has the simplest doping, highest stability and is a relatively p-typed system when the Sm−Hi spacing is closer. The hole conductivity of the Zn34 SmHi O36 -doped system in the z-axis direction is high with no external strain. The magnetic mechanism in the doped system is differs from the traditional theory ofmagnetic source between distinct ions.